Effectiveness of preventive interventions and Randomised Controlled Trials in Occupational Health: an overview of the last five decades: Preventive interventions and Randomised Controlled Trials in Occupational Health - Mattioli, Stefano; Verbeek, Jos; Mattei, Simone; Curti, Stefania (La Medicina del Lavoro, 2021)
Introduction: Evidence-Based Medicine, as a new scientific paradigm, modified the approach to diagnosis, treatment and prevention of diseases based on the best available scientific evidence synthesized in systematic reviews since the last decade of the past century. To evaluate its influence, we assessed the trend in the number and proportion of randomised controlled trials (RCTs) and systematic reviews of preventive interventions in occupational health (OH) over the last five decades. Methods: PubMed has been searched using established search filters regarding occupational determinants of diseases, OH preventive interventions, RCTs and systematic reviews. The number of hits were assessed per decade. We estimated the number of pertinent studies in the systematically recruited samples of retrieved citations. Results: Over the years, the number of studies concerning the effectiveness of preventive interventions in OH increased 3.5-fold from 986 in 1970-1979 to 3,428 in 2010-2019. RCTs of preventive interventions increased more than 60-fold from 6 in the seventies to 370 in the last decade. Systematic reviews first appeared at the end of the past century with a 30-fold increase (from 4 to 120) over the last three decades. Discussion: The number of high-quality studies, such as RCTs and systematic reviews evaluating the effectiveness of preventive interventions in OH, has increased more rapidly than other studies on this topic. The Evidence-Based Medicine philosophy, diffused by researchers worldwide, has promoted the evaluation of the effectiveness of preventive interventions in OH.